Is Yahweh a divine Delilah: An intertextual reading of 1 Kings 22 in light of Jeremiah 20 and Judges 16 - Malan, Morné (Stellenbosch theological journal, 2019)
It is commonly accepted that God is loving, honest, and would not purposefully deceive us to secure a harmful result or any result for that matter. 1 Kings 22:20, 22 and Jeremiah 20:7, 10 seem to represent texts that would suggest otherwise. The first is a text wherein a prophet (Michaiah ben Imlah) states to his king that God has facilitated the deception of four hundred of his other prophets, so that he (the king) may be enticed (or deceived) into his death. The second presents us with a text in which a prophet (Jeremiah) accuses God of enticing (or deceiving) him into the vocation of prophet. Finally, another text which seems to be related to these two is Judges 16:5, whilst this text would appear to have little to do with the others at first glance, after discussing the various connections between all three, a relationship between them will become more plausible. In this paper a literary (and descriptive) rather than a theological (normative) approach to the texts is proposed. It will address such matters as the juxtaposition of the words יכל and פתה as well as similarities in content both narratologically and formally. In doing so, it is theorized that a greater understanding of the specific terminology will be gained. Having discerned the meaning of the terms used, it is hoped that it will provide us more insights into what is happening, and the implications thereof within each text as a literary unit within a greater whole will be gained.